SCFJFK is functionally linked to obesity and metabolic syndrome. (11th June 2021) - He, Lin; Yan, Ruorong; Yang, Ziran; Zhang, Yue; Liu, Xinhua; Yang, Jianguo; Liu, Xujun; Liu, Xiaoping; Xia, Lu; Wang, Yue; Wu, Jiajing; Wu, Xiaodi; et al.
Abstract: Dysregulation of lipid metabolism could lead to the development of metabolic disorders. We report here that the F‐box protein JFK promotes excessive lipid accumulation in adipose tissue and contributes to the development of metabolic syndrome. JFK transgenic mice develop spontaneous obesity, accompanied by dyslipidemia, hyperglycemia, and insulin resistance, phenotypes that are further exacerbated under high‐fat diets. In contrast, Jfk knockout mice are lean and resistant to diet‐induced metabolic malfunctions. Liver‐specific reconstitution of JFK expression in Jfk knockout mice leads to hepatic lipid accumulation resembling human hepatic steatosis and nonalcoholic fatty liver disease. We show that JFK interacts with and destabilizes ING5 through assembly of the SCF complex. Integrative transcriptomic and genomic analysis reveals that the SCF JFK ‐ING5 axis interferes with AMPK activity and fatty acid β‐oxidation, leading to the suppression of hepatic lipid catabolism. Significantly, JFK is upregulated and AMPKα1 is down‐regulated in liver tissues from NAFLD patients. These results reveal that SCF JFK is a bona fide E3 ligase for ING5 and link the SCF JFK ‐ING5 axis to the development of obesity and metabolic syndrome. SYNOPSIS: JFK destabilizes ING5 through assembly of the SCF complex. SCF JFK ‐ING5 axis interferes with AMPK activity and fatty acid β‐oxidation to regulate hepatic lipid metabolism, supporting a functional link of JFK to the development of obesity and NAFLD. JFK promotes excessive lipid accumulation and contributes to the development of obesity and metabolic syndrome in mice. SCF JFK acts as an E3 ligase to destabilize ING5. SCF JFK ‐ING5 axis interferes with AMPK activity and fatty acid β‐oxidation to regulate hepatic lipid metabolism. JFK is upregulated in liver tissues from NAFLD patients. Abstract : JFK destabilizes ING5 through assembly of the SCF complex. SCF JFK ‐ING5 axis interferes with AMPK activity and fatty acid β‐oxidation to regulate hepatic lipid metabolism, supporting a functional link of JFK to the development of obesity and NAFLD.